Towards Justice and Prosperity: Progressive Legal Study of Countering Illegal, Unreported and Unregulated Fishing - Asis, Abd; Chakrabarty, Shambhu Prasad; Yunus, Ahsan; Hehanussa, D. J. A.; Lewerissa, Yanti Amelia (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
Illegal, Unreported, and Unregulated (IUU) fishing poses a significant threat to Indonesia's vast marine resources, contributing to economic losses, environmental degradation, and the marginalization of coastal communities. Although Indonesia has adopted penal and non-penal instruments to counter IUU fishing, the current legal approach remains largely reactive and fragmented, with law enforcement focusing on low-level actors while systemic drivers and corporate beneficiaries remain untouched. The article's strength lies in its integration of progressive law with Islamic legal principles, providing a unique perspective that emphasizes justice, human welfare, and sustainability. This article employs a normative juridical method, using a statute approach, case approach, conceptual approach, and comparative approach to Islamic legal principles such as maslahah mursalah and hisbah. The results shows that a holistic and human-centered legal approach is essential to restore equity, increase deterrence, and ensure sustainable fisheries management. The novelty of this research lies in formulating a concrete legal reconstruction model that operationalizes progressive justice and Islamic legal teleology as integrated instruments for future reform of Indonesia’s fisheries legal regime. This article contributes to the discourse on legal reform in environmental governance, offering practical insights for policymakers and legal practitioners in Indonesia and beyond.